Arimoclomol: a potential therapy under development for ALS - Lanka, Veena; Wieland, Scott; Barber, Jack; Cudkowicz, Merit (Expert opinion on investigational drugs, 2009)
Arimoclomol, an amplifier of heat shock protein expression involved in cellular stress response, has emerged as a potential therapeutic candidate in amyotrophic lateral sclerosis (ALS) in recent years. Treatment with arimoclomol was reported to improve survival and muscle function in a mouse model of motor neuron disease. Several single- and multiple-dose safety studies have been completed in healthy control subjects. A 3-month Phase IIa study in people with ALS demonstrated safety at dosages up to 300 mg/day and another study is currently recruiting participants with familial ALS caused by mutations in the superoxide dismutase gene. We review the rationale for testing arimoclomol in sporadic and familial ALS in the context of available safety and pharmacokinetic data. Published and unpublished literature relative to the drug in the past two decades is discussed. The current review attempts to bring together our existing understanding of the actions of arimoclomol with the disease profile of ALS. The pharmacological profile of arimoclomol and the available preclinical data make it a promising therapeutic possibility in ALS.